Using Voronoi diagrams to describe tactical behaviour in invasive team sports: an application in basketball - Lopes, Antonio; Fonseca, Sonia; Lese, Roland; Baca, Arnold (Cuadernos de Psicología del Deporte, 2015)
Team sports are recognized as dynamic systems of interaction, where individual and collective patterns of behaviour emerge from a confluence of multiple constraints on the players. Players’ distribution on the field is often associated with tactical options, strategic decisions, and principles. Hence, the analysis of positional data has gained relevance and is now a hot topic in sport science research, feeding the interests of researchers, analysts and coaches. Recent studies tried to characterize teams’ and players’ tactical behaviour using variables derived from their spatial distribution (e.g., the area of the convex hull). The Voronoi diagrams (VD) have been introduced for the analysis of the spatial organization in team sports as it allows, unlike other models, defining the dominant region of both players and teams. This study considered the application of VD to describe o;ensive tactical behaviour in basketball. For this purpose, a formal game between two teams of Austrian basketball talents was observed, from where 19 ofensive sequences were selected for analysis. The results indicate that the percentage of area occupied by each team, at each instant, can be considered to describe teams’ patterns of spatial organization during a positional attack, allowing to classify and distinguish transition phase and organized phase. This approach may also help to reduce the time spent in video analysis by coaches, giving them more time to prepare training plans and sessions in order to improve the tactical and strategic performance of their teams.